The English Medieval First-Floor Hall: Part 1 – Scolland's Hall, Richmond, North Yorkshire. Issue 1 (2nd January 2018) - Hill, Nick; Gardiner, Mark
Abstract : A new survey of Scolland's Hall in Richmond Castle identifies it as an early example of an integrated hall, chamber and garderobe. The hall was entered at one corner and the entrance to the chamber was at the opposite corner, suggesting that it had a low end and high end of the conventional form better known from buildings of the thirteenth century and later. The chamber was relatively small and had a mural fireplace set in the middle of the longer wall. It had a door to a projecting balcony, while a further balcony was provided overlooking the River Swale alongside the undercroft. The building is dated to the 1080s. It is argued that the features which appear to be unusual at Scolland's Hall – the location of the hall at first-floor level, the organization into a low and high end, the integration of the hall and chamber, and the use of viewing balconies – have parallels in other near-contemporary buildings.